2008
DOI: 10.4141/cjps07112
|View full text |Cite
|
Sign up to set email alerts
|

Impact of agronomic factors on seed yield formation and quality in flax

Abstract: . 2008. Impact of agronomic factors on seed yield formation and quality in flax. Can. J. Plant Sci. 88: 485Á500. Flaxseed is known to have significant health benefits in human nutrition and when included in animal rations. There is pressing need to improve flaxseed production to meet the growing demand. The objective was to study the effects of three seeding rates (22, 45 and 67 kg ha(1 ), two seeding dates (early May and late May), three rates of nitrogen (66, 100 and 133% of recommended) and three cultivars … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
26
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 19 publications
(36 reference statements)
12
26
2
2
Order By: Relevance
“…It is widely accepted that smaller stems are more likely to ret uniformly and this is another potential benefit to increasing seeding rate. Increasing seeding rate did not significantly increase seed yields; this lack of response is similar to previous results (Albrechtsen and Dybing 1973;Gubbels and Kenaschuk 1989;Stevenson and Wright 1996;Lafond et al 2008). The smaller stems and higher fibre yield resulting from higher seeding rates indicate that seeding rate should be increased if the value of the extra fibre exceeds the cost of the seed.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…It is widely accepted that smaller stems are more likely to ret uniformly and this is another potential benefit to increasing seeding rate. Increasing seeding rate did not significantly increase seed yields; this lack of response is similar to previous results (Albrechtsen and Dybing 1973;Gubbels and Kenaschuk 1989;Stevenson and Wright 1996;Lafond et al 2008). The smaller stems and higher fibre yield resulting from higher seeding rates indicate that seeding rate should be increased if the value of the extra fibre exceeds the cost of the seed.…”
Section: Resultssupporting
confidence: 77%
“…Our results differed from those of Lafond et al (2008), who found early seeding increased linseed seed yields in more southerly areas with later planting being favoured in more northerly areas Thompson et al (1988) also found that earlier seeding improved flax yields North Dakota. The lack of seed yield reduction noted in this study may be due in part to the colder than normal weather occurring in 2004 (Table 1), which would make the climate for our sites similar to that of the northern areas reported by Lafond et al (2008). We found that fibre content and available yield were higher for the later seeding dates (Tables 2 and 3) resulting in a 170 kg ha (1 , or 53%, increase in fibre yield.…”
Section: Resultscontrasting
confidence: 57%
See 2 more Smart Citations
“…However, plants are cultured in different environments where they are exposed to various climate conditions and soils conditions with a direct repercussion on the seed filling and its final composition (Dilman and Hopper, 1943;Dybing et al, 1966;Kirkhus et al, 2013;Lafond et al, 2008;Painter et al, 1944;Westcott and Muir, 2003). In fact, several factors comprising temperature, rainfall, light, drought, ozone exposure, nitrogen deprivation, fertilizers may influence the nutritional quality of oilseeds (Baldini et al, 2002;Flagella et al, 2002;Green, 1986;Harris et al, 1978;Rahimi et al, 2011;Tripathi and Agrawal, 2013).…”
mentioning
confidence: 99%